UKRAINIAN GEOPOLITICAL PRIORITIES OF PRESIDENT ELECTION CAMPAIGN IN UKRAINIAN 2010 - Прокопова, О.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article the geopolitical priorities of Ukrainian in the manifests of candidates in President are analyzed. On the basis of analyze of geopolitical priorities in presidents’ of programs and state of public consciousness the conclusion is made as to the prospects of our state participation in top international systems.